Golgi screen identifies the RhoGEF Solo as a novel regulator of RhoB and endocytic transport. (6th January 2023) - Lungu, Cristiana; Meyer, Florian; Hörning, Marcel; Steudle, Jasmin; Braun, Anja; Noll, Bettina; Benz, David; Fränkle, Felix; Schmid, Simone; Eisler, Stephan A.; Olayioye, Monilola A.
Abstract: The control of intracellular membrane trafficking by Rho GTPases is central to cellular homeostasis. How specific guanine nucleotide exchange factors and GTPase‐activating proteins locally balance GTPase activation in this process is nevertheless largely unclear. By performing a microscopy‐based RNAi screen, we here identify the RhoGEF protein Solo as a functional counterplayer of DLC3, a RhoGAP protein with established roles in membrane trafficking. Biochemical, imaging and optogenetics assays further uncover Solo as a novel regulator of endosomal RhoB. Remarkably, we find that Solo and DLC3 control not only the activity, but also total protein levels of RhoB in an antagonistic manner. Together, the results of our study uncover the first functionally connected RhoGAP‐RhoGEF pair at endomembranes, placing Solo and DLC3 at the core of endocytic trafficking. Abstract : The control of intracellular membrane trafficking by Rho GTPases is a poorly understood process that is central to cellular homeostasis. Using the morphology of the Golgi complex a readout for Rho activity, we here identify Solo as a RhoGEF protein that counteracts the cellular functions of the DLC3 RhoGAP. We find that Solo localizes to RhoB positive endosomes and regulates the transport of RhoB‐dependent cargo such as epidermal growth factor receptor. Remarkably, Solo and DLC3 do not only control the activity, but also total protein levels of RhoB in an antagonistic manner. These results uncover the first functionally connected RhoGAP‐RhoGEF pair at endomembranes and place Solo and DLC3 at the core of endocytic trafficking.